Current features and mortality risk factors in cardiogenic shock due to miocardial infarction in a Latin-american hospital - Guzmán-Rodríguez, Rosario (2020)
Objective. To know the clinical characteristics and determine the related factors to higher in-hospital mortality in patients with cardiogenic shock (CS) due to myocardial infarction in a Peruvian reference hospital. Materials and methods. We conducted a prospective single-center cohort study, to evaluate the clinical characteristics, treatment, and complications of patients with CS due to myocardial infarction from March 2019 to August 2020 at the Instituto Nacional Cardiovascular INCOR. Factors related to higher in-hospital mortality and during follow-up were evaluated. Also, the IABP shock II score was applied to stratify the cohort. Results. Forty patients were included in the study, 75% of cases were due to left ventricular dysfunction, most of the men and with a median age of 75 (69-82) years. Fifty percent of cases presented CS after admission to the emergency room. Patients stratified by the IABP shock II score as low, intermediate, and high risk, had in-hospital mortality of 37.5%, 71.4%, and 91.6% respectively. In a hospital, mortality was 70%, higher in women, in those over 75 years old, and in those who developed CS during their hospitalization. Serum lactate > 4 mmol/L in univariate analysis was associated with higher mortality risk (HR: 2.8; IC:1.6-3.6, p=0.009). Survival to the end of the study was 12.8%. Conclusions. CS due to myocardial infarction is a clinical entity with high mortality in spite of revascularization and the available treatment in our reality. The highest mortality predictor was the serum lactate at admission >4 mmol/L. The IABP shock II score showed to be an accurate parameter to stratify the death risk in our population.